Determination of Diffusion Coefficient and Number of Electrons Transferred Through Ultramicro Platinum Electrode - OZTURK, FUNDA; SECKEN, NILGUN; SEDA YUCEL, A. (Asian Journal of Chemistry, 2010)
This study aims to introduce the cyclic voltammetry (CV) with ultramicro platinum electrode technique, enable their comprehension through starting from the known conventional CV method and determine the differences between the conventional CV and the cyclic voltametry with ultramicro platinum electrode. The CV obtained through the usage of micro electrode and the voltammograms obtained through the cyclic voltametry with ultramicro platinum electrode were compared and contrasted. The diffusion coefficient (D) and the number of electrons transferred (n) were calculated with the help of the CV results obtained through the utilization of chronoamperometer and ultramicro platinum electrode. In this study, using the ultramicro platinum electrode, the diffusion coefficient of the azobenzene was calculated as 9.89 × 10-6a ± 8.17 × 10-7 and that of ferrocene was calculated as 1.12 × 10-5 ± 4.69 × 10-7. The number of electrons transferred for both substances was found to be 1.